Revised Ordinances and Resolutions of the City Council of Salt Lake City, in the Territory of Utah, with Congressional and Territorial Laws on Townsites and Great Salt Lake City Charter, and Amendments, at 161-162, ch. 48, § 1 (1875) - (:unkn) unknown (My University, 1875)
Be it ordained, by the City Council of Salt Lake City, that it shall not be lawful for any person or persons to keep, sell or give away, gunpowder, gun-cotton, or nitro-glycerine, in any quantity without permission of the City Council; Provided, any person may keep, for his own use, not exceeding five pounds of gun powder, one pound of gun cotton, or one ounce of nitro-glycerine.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER